Body-Weight and Women's Hours of Work: More Evidence That Marriage Markets Matter - Shoshana Grossbard; Sankar Mukhopadhyay (Institute of Labor Economics (IZA), 2017)
Higher body-weight (BMI) can affect labor supply via its effects on outcomes in both labor markets and marriage markets. To the extent that it is associated with lower prospects of being in couple and obtaining intra-couple transfers, we expect that higher BMI will increase willingness to supply labor in labor markets, especially for women. We use US panel data from the NLSY79 and NLSY97 to examine whether body weight influences hours of work in the labor market. We use sibling BMI as an instrument for own BMI to address potential endogeneity of BMI in hours worked. We find that White women with higher BMI work more. This is true for both single and married White women. Results for other groups of women and men produce mixed results. The extended analysis suggests that what drives the relationship between BMI and hours worked is not lower market wages earned by high-BMI women, but rather lower spousal transfers to married women or lower expected intra-marriage transfers to single women.
Keywords: J22; I12; J12; 330; obesity; labor supply; marriage prospects; intra-household division of resources